A comparison of Listeria monocytogenes contamination in bagged and un-bagged lettuce in supermarkets. (December 2020) - Kyere, Emmanuel O.; Qiu, Goh Wan; Md Zain, Siti Norbaizura; Palmer, Jon; Wargent, Jason J.; Fletcher, Graham C.; Flint, Steve
Abstract: The popularity of bagged salads sold in the market has increased due to their ease of transportation and convenience but there are food safety risks. In this study, we examined the prevalence of Listeria monocytogenes ( L. monocytogenes ) in 100 samples of ready-to-eat bagged and non-bagged lettuces sold in supermarkets in New Zealand. We found five samples tested positive for L . monocytogenes and two further bagged lettuce samples which tested positive for other Listeria species. None of the un-bagged lettuce samples were contaminated with Listeria . The results of this survey indicate a higher microbial risk associated with consumption of bagged salads. This underlines the need for the fresh produce industry to ensure efficient sanitization of their produce before bagging to reduce the risk of Listeria contamination. Highlights: The prevalence of Listeria in lettuces sold in supermarkets in a major city in NZ was found to be 7%. Listeria contamination in bagged lettuce was higher than un-bagged lettuces sold in supermarkets. The growing reports of Listeria in lettuce is supported by the results of this study.